Linking air-void system and mechanical properties to salt-scaling resistance of concrete containing slag cement. (November 2019) - Amini, Kamran; Vosoughi, Payam; Ceylan, Halil; Taylor, Peter
Abstract: This paper is focused on correlating salt-scaling resistance to material performance of concrete made with various water-to-cement ratios (w/cm), ternary blends of slag cement and fly ash, and air contents. The fly ash incorporation was kept constant at 20% cement content replacement for all mixes. The material performance of the mixtures was evaluated using air-void system, sorptivity, abrasion, compressive strength, and depth-sensing indentation (DSI) tests. Test results show that effect of concrete properties, i.e., sorptivity, surface hardness, and air content on salt scaling resistance of concrete is relative to mixture proportion. For a w/cm of 0.55 the average total salt scaling after 45 F-T cycles was found about 80% higher than that of mixes made with w/cm of 0.35. The results associated with mixtures made with slag cement were found misleading, since they exhibited improved mechanical properties, while lowered salt-scaling resistance. In addition, 3–6% of air entrainment appeared beneficial for concrete mixtures made with w/cm of 0.55, when subjected to high potential salt scaling environments.